2005
DOI: 10.1590/s0100-40422005000500020
|View full text |Cite
|
Sign up to set email alerts
|

Constituintes químicos de Luehea divaricata Mart. (Tiliaceae)

Abstract: Recebido em 24/8/04; aceito em 17/2/05; publicado na web em 11/7/05 CHEMICAL CONSTITUENTS OF Luehea divaricata Mart. (TILIACEAE). Chemical studies of the leaves of L. divaricata afforded 3β-p-hydroxybenzoyl-tormentic acid, a triterpene with an ursene-type skeleton, a mixture whose main compound was an oleanene derivative, the maslinic acid, a C-glycoside flavone, vitexin and glucopyranosylsitosterol. A flavonoid, characterized as (-)-epicatechin, which belongs to the flavan-3-ol class, was isolated from the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
13

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 6 publications
(13 reference statements)
1
39
0
13
Order By: Relevance
“…Obtidos os valores de CIM e CBM, os extratos vegetais de E. anomala e P. salutare foram avaliados quanto a sua ação antimicrobiana de acordo com os valores de CIM contra os patógenos estudados onde extratos que apresentam CIM<100 µg/mL têm potencial antimicrobiano promissor (bom), CIM entre 100 -500 µg/mL possui atividade inibitória moderada, CIM entre 500 -1.000 µg/mL apresenta atividade inibitória fraca e extratos que apresentaram CIM superior a 1.000 µg/mL são inativos frente aos patógenos (Fabry et al, 1998;Holetz et al, 2002;Dall'Agnol et al, 2003;Tanaka et al, 2005;Chavasco et al, 2014).…”
Section: Atividade Antimicrobianaunclassified
“…Obtidos os valores de CIM e CBM, os extratos vegetais de E. anomala e P. salutare foram avaliados quanto a sua ação antimicrobiana de acordo com os valores de CIM contra os patógenos estudados onde extratos que apresentam CIM<100 µg/mL têm potencial antimicrobiano promissor (bom), CIM entre 100 -500 µg/mL possui atividade inibitória moderada, CIM entre 500 -1.000 µg/mL apresenta atividade inibitória fraca e extratos que apresentaram CIM superior a 1.000 µg/mL são inativos frente aos patógenos (Fabry et al, 1998;Holetz et al, 2002;Dall'Agnol et al, 2003;Tanaka et al, 2005;Chavasco et al, 2014).…”
Section: Atividade Antimicrobianaunclassified
“…(Tiliaceae) is a big-sized tree (15 to 25 m); it is popularly known as açoita-cavalo and may be found in several Brazilian states, from Rio Grande do Norte to Rio Grande do Sul (Alice et al 1995;Lorenzi 2000). According to Tanaka et al (2005), Luehea leaves are sold as phytotherapic products for dysentery, leucorrhea, rheumatism, blennorrhoea, and tumors. The infusion of its flowers is used to cure bronchitis, while the root has depurative assets.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, Brazilian research characterized two triterpenes (a tormentic acid derivative and maslinic acid), which were obtained from a methanolic extract of L. divaricata leaves (Tanaka, Vidotti, Silva, 2003), but the biological properties of these compounds have not been assessed. The same research group identified a flavonoid, epicatechin, from a methanolic extract of the leaves of L. divaricata, which demonstrated antimicrobial activity against Staphylococcus aureus (250-500 μg/mL) (Tanaka et al, 2005). Coelho de Souza et al (2004) also verified the antimicrobial activity of a methanolic extract (50 mg/mL) of the aerial parts of L. divaricata.…”
Section: Introductionmentioning
confidence: 90%